Asymmetric Impact of Oil Prices and Stock Prices on Bank’s Profitability: Evidence from Saudi Islamic Banks - Md Fouad Bin Amin (International Journal of Islamic Economics and Finance (IJIEF), 2022)
The soundness of financial institutions including banks depends on both internal factors and external factors. The profitability of the banks largely affected by external shocks like oil prices and stock prices. As an oil-exporting country, Saudi economy particularly its banking sector largely rely on the oil prices. This study examines the asymmetric impact of oil prices and stock prices on Saudi Islamic banks’ profitability for the period 2000-2020. Two Saudi Islamic banks’ profitability is examined by the factors like Return on Equity (ROE) and Return on Assets (ROA) with the help of a nonlinear autoregressive distributed lag (NARDL) model. The estimated results are observed to be unbiased and robust. The results of this study show that OILP and STOCKP have significant role in determining the Islamic banks’ profitability in Saudi Arabia. Both higher oil prices and stock prices have positive influence on ROE and ROA of Saudi Islamic banks. This study suggest that development and efficiency of Saudi stock market is important and macroeconomic policy should support the country’s economic diversification. The management of Islamic banks need to focus on effective risk assessment and market monitoring tools to face the fluctuation of oil prices and their stock prices as these factors affect their profitability. Besides, Saudi Islamic banks need to diversify their investment portfolios into more productive and export oriented private sectors such as Small Medium Enterprises (SMEs). This strategic policy will enable Islamic banks to absorb any future shock of oil prices without affecting their profitability.